Workplace Mental Health Training in Health Care: Key Ingredients of Implementation. (December 2018) - Moll, Sandra E.; VandenBussche, Jessica; Brooks, Katelyn; Kirsh, Bonnie; Stuart, Heather; Patten, Scott; MacDermid, Joy C.
Objectives: Despite growing awareness of the importance of workplace mental health training and an increasing number of educational resources, there is a gap in knowledge regarding what shapes training effectiveness. The purpose of this study was to compare and describe the active ingredients of 2 workplace mental health education programs for health care workers. Methods: Within the context of a randomized clinical trial, a multimethod process evaluation was conducted to explore key process elements shaping implementation outcomes: the innovation, service recipients, service providers, and the organizational context. Data collection included descriptive statistics regarding program participation, postprogram interviews with a purposive sample of 18 service recipients, 182 responses to open-ended questions on postgroup and follow-up surveys, and field journal reflections on the process of implementation. Data analysis was informed by an interpretive description approach, using a process evaluation framework to categorize responses from all data sources, followed by within and cross-case comparison of data from both programs. Results: Five key forces shaped the implementation and perceived outcomes of both programs: a contact-based education approach, information tailored to the workplace context, varied stakeholder perspectives, sufficient time to integrate and apply learning, and organizational support. The Beyond Silence program provided more opportunity for contact-based education, health care–specific content, and in-depth discussion of diverse perspectives. Conclusions: To increase mental health literacy and reduce stigma, workplace training should be based on best practice principles of contact-based education, with contextually relevant examples and support from all levels of the organization.